E-Monitoring Pendeteksi Cuaca dan Kelembaban Tanah untuk Meningkatkan Hasil Panen Petani Sawi Berbasis Internet of Things (IoT) - Syahzillah, Anggie; Rizky, Firahmi (Lembaga Riset Mutiara Akbar, 2025)
Mustard greens are a horticultural crop that is highly dependent on environmental conditions, particularly weather and soil moisture. Climate irregularities and errors in irrigation management often lead to decreased crop productivity. This research aims to design and develop an Internet of Things (IoT)-based e-monitoring system capable of detecting weather conditions and soil moisture in real time. This system uses temperature, air humidity, and soil moisture sensors integrated with a microcontroller and Wi-Fi module to transmit data to a web-based monitoring platform or application. Test results show that the system is capable of providing accurate and responsive information to environmental changes, enabling farmers to make informed decisions regarding watering times and plant treatments. With this system, it is hoped that mustard greens productivity can significantly increase through more efficient and data-driven land management.